Issues of using new approaches to teaching historical science - Usmonaliyeva, Risolat (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article discusses the problems of applying innovative methods of teaching history in secondary schools in accordance with the modernization process. Methodical recommendations on the use of interactive methods of teaching history and the organization of independent work of pupils are provided